Education for All: Developing Learning Strategies that Prioritize Equity and Accessibility - Darwin, David (PT. Hafasy Dwi Nawasena, 2025)
Abstract Inclusive education guarantees the rights of every individual, including children with special needs (ABK), to obtain quality education services without discrimination. Although legal support has been provided through Law No. 20 of 2003 and Law No. 19 of 2011, the implementation of inclusive education at the school level still faces various challenges. This study aims to identify obstacles and formulate inclusive learning strategies based on Universal Design for Learning (UDL) in a blended learning approach. The study was conducted using a descriptive qualitative method at SDN 1 Pulau Rinca, NTT, through observation, interviews, and document studies. The results show that the learning approach is still predominantly lecture-based, without adaptive media and assistive technology support. Teachers have not received UDL training, while facilities and infrastructure do not support the needs of ABK students. However, positive potential emerged in the form of social empathy of regular students towards ABK friends. UDL-based blended learning has been proven to be able to increase student engagement and learning outcomes by providing variations in how to deliver material, express understanding, and encourage active participation. Therefore, the systemic implementation of UDL, teacher training, provision of inclusive facilities, and strengthening collaboration between schools and parents are the keys to creating a more equitable, adaptive, and humane education.